Activation of the NLRP3 inflammasome by group B streptococci - Costa, Alessandro (2012)
Group B streptococcus (GBS) is a frequent agent of life-threatening sepsis and meningitis in neonates and adults with predisposing conditions. We tested the hypothesis that activation of the inflammasome, an inflammatory signaling complex, is involved in host defenses against this pathogen. We show here that murine bone marrow-derived conventional dendritic cells responded to GBS by secreting IL-1β and Il-18. IL-1β release required both pro-IL-1β transcription and caspase-1-dependent proteolytic cleavage of intracellular pro-IL-1β. Dendritic cells lacking the TLR adaptor MyD88, but not those lacking TLR2, were unable to produce pro-IL-1β mRNA in response to GBS. Pro-IL-1β cleavage and secretion of the mature IL-1β form depended on the NOD-like receptor family, pyrin domain containing 3 (NLRP3) sensor and the apoptosis-associated speck-like protein containing a CARD (ASC) adaptor. Moreover, activation of the NLRP3 inflammasome required GBS expression of β-hemolysin, an important virulence factor. We further found that mice lacking NLRP3, ASC or caspase-1 were considerably more susceptible to infection than wild-type mice. Our data link the production of a major virulence factor by GBS with the activation of a highly effective anti-GBS response triggered by the NLRP3 inflammasome.